Adoption of weather-index insurance: Learning from willingness to pay among a panel of households in rural Ethiopia - Hill, Ruth Vargas; Hoddinott, John F.; Kumar, Neha (Wiley, 2013)
In this article we examine which farmers would be early entrants into weather‐index insurance markets in Ethiopia, were such markets to develop on a large scale. We do this by examining the determinants of willingness to pay for weather insurance among 1,400 Ethiopian households that have been tracked for 15 years as part of the Ethiopian Rural household Survey. This provides both historical and current information with which to assess the determinants of demand. We find that educated, wealthier individuals are more likely to purchase insurance. Risk aversion is associated with low insurance take‐up suggesting that models of technology adoption can inform the purchase and spread of weather index insurance. We also assess how willingness to pay varied as two key characteristics of the contract were varied and found that basis risk reduces demand for insurance particularly when the price of the contract is high, and that provision of insurance through groups is preferred by female headed households and individuals with lower levels of education.